Search for transient variations of the fine structure constant and dark matter using fiber-linked optical atomic clocks. (4th September 2020) - Roberts, B M; Delva, P; Al-Masoudi, A; Amy-Klein, A; Bærentsen, C; Baynham, C F A; Benkler, E; Bilicki, S; Bize, S; Bowden, W; Calvert, J; Cambier, V; et al.
Abstract: We search for transient variations of the fine structure constant using data from a European network of fiber-linked optical atomic clocks. By searching for coherent variations in the recorded clock frequency comparisons across the network, we significantly improve the constraints on transient variations of the fine structure constant. For example, we constrain the variation to | δα / α | < 5 × 10 −17 for transients of duration 10 3 s. This analysis also presents a possibility to search for dark matter, the mysterious substance hypothesised to explain galaxy dynamics and other astrophysical phenomena that is thought to dominate the matter density of the universe. At the current sensitivity level, we find no evidence for dark matter in the form of topological defects (or, more generally, any macroscopic objects), and we thus place constraints on certain potential couplings between the dark matter and standard model particles, substantially improving upon the existing constraints, particularly for large (≳10 4 km) objects.